2016
DOI: 10.3390/nu8040219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postprandial Blood Pressure on Gait Parameters in Older People

Abstract: Postprandial hypotension (PPH), a fall in systolic blood pressure (SBP) within 2 h of a meal, may detrimentally affect gait parameters and increase the falls risk in older people. We aimed to determine the effects of postprandial SBP on heart rate (HR), gait speed, and stride length, double-support time and swing time variability in older subjects with and without PPH. Twenty-nine subjects were studied on three days: glucose (“G”), water and walk (“WW”), glucose and walk (“GW”). Subjects consumed a glucose dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Gray-Miceli et al found that older adults with OH in long-term care were less likely to walk in a steady line 25 while Nair et al demonstrated that postprandial hypotension was associated with changes in gait speed and double support time. 26 Older adults with a history of falls and OH have also been shown to spend longer in stance than nonfallers and had lower stance and swing time variability than non-OH fallers but not controls. 27 This study therefore adds significantly to existing literature in this field by including a large, well-described population-based cohort of community-dwelling adults, using continuous beat-to-beat values of orthostatic BP alongside spatiotemporal gait analysis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Gray-Miceli et al found that older adults with OH in long-term care were less likely to walk in a steady line 25 while Nair et al demonstrated that postprandial hypotension was associated with changes in gait speed and double support time. 26 Older adults with a history of falls and OH have also been shown to spend longer in stance than nonfallers and had lower stance and swing time variability than non-OH fallers but not controls. 27 This study therefore adds significantly to existing literature in this field by including a large, well-described population-based cohort of community-dwelling adults, using continuous beat-to-beat values of orthostatic BP alongside spatiotemporal gait analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Existing research is limited to three studies with fewer than 50 participants. Gray‐Miceli et al found that older adults with OH in long‐term care were less likely to walk in a steady line while Nair et al demonstrated that postprandial hypotension was associated with changes in gait speed and double support time . Older adults with a history of falls and OH have also been shown to spend longer in stance than nonfallers and had lower stance and swing time variability than non‐OH fallers but not controls .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies investigating PPH have utilised an oral [11,12,13,16,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73], and/or ID glucose [14,18,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88] load that induces a substantial fall in BP. There have been a total of 58 studies related to effects of glucose on postprandial BP in a range of cohorts including health [11,12,14,16,18,39,40,41...…”
Section: Nutritive Sweetenersmentioning
confidence: 99%
“…Due to its ability to induce a prominent hypotensive response, several studies investigating non-pharmacological [63,67,68,84,86,87] and pharmacological [18,55,57,58,59,60,61,64,65,83,85,88] approaches to the management of PPH have used glucose as test meals. Interventions based on slowing gastric emptying [63,84] and small intestinal absorption of nutrients [82] attenuate the postprandial fall in BP.…”
Section: Nutritive Sweetenersmentioning
confidence: 99%
See 1 more Smart Citation